A cognitive psychology of mass communication - Sanborn, Fred W.; Harris, Richard Jackson (New York Routledge, 2019)
"In a constantly changing media landscape, A Cognitive Psychology of Mass Communication is the go-to text for any course that examines mass communication from a psychological perspective. Now in its seventh edition, the book continues its exploration of how our experiences with media affect the way we acquire and process knowledge about the world and how this knowledge influences our attitudes and behavior. Updates include end-of-chapter suggestions for further reading, new research and examples for a more global perspective, as well as an added emphasis on the power of social media in affecting our perceptions of reality and ourselves. While including real-world examples, the book also integrates psychology and communication theory along with reviews of the most up-to-date research. The text covers a diversity of media forms and issues, ranging from commonly discussed topics such as politics, sex, and violence, to lesser-studied topics, such as emotions and prosocial media. The accompanying companion website also includes resources for both instructors and students For students: - Chapter outlines, summaries, and review questions - Useful links For instructors: - Guidelines for in-class discussions - Sample syllabus Readers will be challenged to become more sensitized and to think more deeply about their own media use as they explore research on behavior and media effects. Written in an engaging, readable style, the text is appropriate for graduate or undergraduate audiences"--
Mass communication in our wired society: the changing media landscape -- Research and theory in mass communication: how are media studied scientifically? -- The psychology of mass communication: thinking about our media use -- Emotions and media: music and sports as exemplars -- Media portrayals of groups: distorted social mirrors -- Advertising: baiting, catching, and reeling us in -- News: setting an agenda about the world -- Politics: using news and advertising to win elections -- Violence: media mayhem matters -- Sex: is tuning in turning us on? sexuality through a media lens -- Socially positive media: teaching good things to children (and the rest of us).
Includes bibliographical references and indexes.
Keywords: Mass media -- Psychological aspects